Euphony in World Languages - Tambovtsev, Yuri (Lingua Posnaniensis, 2010)
There are many languages in the world but every language has its own sound picture. By the sound picture of a language we mean the distribution of its speech sounds in the speech sound chain. It is very interesting to find the languages which are melodical or euphonic and which are not. Melodicity or euphony is the total of the vowels and sonorant consonants in the speech sound chain of a language. It is also possible to call this total the vocalo-sonorant quotient. Thus, the degree of melodicity is the value of this quotient. Vowels and sonorant consonants constitute the vocalo-sonorant structure of the sound picture of any language. We take into consideration the basic features of sound classes and groups. The basic features consist of the frequency of occurrence of vowels and sonorant consonants in the speech chain. These basic features may be found in any world language. This is why, melodicity is one more language universal. Analysing the value of melodicity, one can construct the typology of distribution of language taxa according to this universal characteristic. Austronesian languages have a great concentration of vowels in the speech sound chain (e.g. maximum – 65.24% in Hawaiian and 69.75% in Samoan). Vocalo-sonorant quotient turned out to be bigger in the following language taxa: Sino-Tibetan family (Burmese – 75.67%), Bantu (Swahili – 76.29%), Afro-Asian family (Neo-Aramaic – 81.47%), Austronesian family (Hawaiian – 83.29%), languages of Australian aboriginals – Nunggubuyu – 85.14%). It means that 85.14% of the Nunggubuyu speech sound chain consists of vowels and sonorant consonants. On the other hand, some of the world languages have the minimum of the concentration of vowels. So, in the Itelmen language (Paleo-Asiatic family) vowels comprise only 32.61%. Let us consider the minimum of the vocalo-sonorant quotient. Thus, in the Adygian language (Caucasian family) this quotient reaches only 54.07%. It should be mentioned that on the average the Caucasian language family has a rather low vocalosonorant quotient – 61.66%. The ordered series of the average of the vocalo-sonorant quotient in different language taxa is the following: Baltic group of Indo-European family – 62.76%; Iranian group of the Indo-European family – 63.95%); Slavonic group – 64.64%; Germanic – 64.78%; Samoyedic family – 65.16%; Finno-Ugric family – 65.57%; Mongolic family – 66.06%; Balkan language unity – 66.18%; Indic group of the Indo-European family – 66.77%; Turkic family – 66.99%; Paleo-Asiatic family – 67.58%; Sino-Tebetan family – 67.63%; Roman group of I-E family – 68.57%; Afro-Asiatic family – 68.96%; Manchu-Tungusic family – 69.54%; Austronesian family – 73.16%; Bantu – 73.40%; Languages of Australian aboriginals – 80.51%. Melodicity, i.e. the total of vowels and sonorant consonants, may be considered a language universal.